The PanCareFollowUp Care Intervention: A European harmonised approach to person-centred guideline-based survivorship care after childhood, adolescent and young adult cancer - van Kalsbeek, Rebecca J; Mulder, Renée L; Haupt, Riccardo; Muraca, Monica; Hjorth, Lars; Follin, Cecilia; Kepak, Tomas; Kepakova, Katerina; Uyttebroeck, Anne; Mangelschots, Marlies; Winther, Jeanette Falck; Loonen, Jacqueline J; et al. (European journal of cancer (Oxford, England, 2022)
BACKGROUND: Long-term follow-up (LTFU) care, although endorsed, is not available for the majority of adult survivors of childhood, adolescence and young adult (CAYA) cancer. Barriers to implementation include lack of time, knowledge, personnel and funding. Sustainable solutions are urgently needed to address the needs of CAYA cancer survivors to improve the quality of life and reduce the burden of late effects on survivors, health care systems and society. The European Union-funded PanCareFollowUp project, initiated by the Pan-European Network for Care of Survivors after Childhood and Adolescent Cancer, was established to facilitate the implementation of person-centred survivorship care across Europe. PATIENTS AND METHODS: The PanCareFollowUp Care Intervention was co-developed with survivors as part of the PanCareFollowUp project. It is a person-centred approach to survivorship care, supported by guidelines and with flexibility to adapt to local health care settings. The Care Intervention consists of three steps: (1) previsit completion of a Survivor Questionnaire (by the survivor) and Treatment Summary (by the health care provider [HCP]), (2) a clinic visit including shared decision-making, and (3) a follow-up call to finalise the individualised Survivorship Care Plan. RESULTS: We developed the key components of the PanCareFollowUp Care Intervention: a PanCareFollowUp Survivor Questionnaire, Treatment Summary template, Survivorship Care Plan template, and educational materials for HCPs and survivors. Wide implementation of the PanCareFollowUp Care Intervention will be supported with a freely distributed Replication Manual on completion of the PanCareFollowUp project. CONCLUSIONS: The PanCareFollowUp Care Intervention will support the implementation of person-centred, guideline-based LTFU care in different health care settings across Europe to improve survivors' health and well-being.
Keywords: Person-centred care; Humans; Long-term follow-up care; přežívající; Cancer Survivors; Quality of Life; mladý dospělý; Cancer survivorship care; Survivors; lidé; přežívající onkologičtí pacienti; období po vyléčení; kvalita života; Adolescent; Childhood cancer survivor; Neoplasms; nádory; Young Adult; Quality of life; Survivorship; Shared decision-making; mladiství